New records of rare butterflies (Lepidoptera: Papilionoidea) in Albania - Ana Nahirnić-Beshkova; Stoyan Beshkov; Predrag Jakšić (Historia naturalis bulgarica, 2022)
Field work conducted in 2016-2019 and 2022 contributed with additional data on 23 relatively rare species in Albania, including the second record of Cacyreus marshalli and the sixth record of Apatura metis. Several new localities are given for Danaus chrysippus, which proved to be not rare on the southern coast of Albania.